The next 10 years for tuberculosis vaccines: do we have the right plans in place? - Meyer, Joel (Expert Rev Vaccines, 2013)
The control of TB is a global health priority. Over the last decade, considerable progress has been made in the field of TB vaccines with numerous vaccine candidates entering the clinic and two candidates now in Phase IIb efficacy trials. Nevertheless, the lack of predictive animal models and biomarkers of TB vaccine efficacy prevents rational vaccine down-selection and necessitates prolonged and expensive clinical efficacy trials in target populations. Advances in molecular technology and progress in the development of human as well as animal mycobacterial challenge models make the identification of one or more immune correlates of protection a genuine prospect over the next decade. Moreover, the increasing pace, extent and coordination of global research efforts in TB promises to broaden understanding and inform the next generation of vaccine candidates against TB as well as related globally important pathogens.